Hegemoni Agama dalam Pendidikan: Euforia Pendidikan Islam Terpadu di Solo Raya - Kusumawati, Dian (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2014)
Integrated Islamic Primary School called by Sekolah Dasar Islam Terpadu / SDIT appeared in the area of religious hegemony in through educational institutions. Community who were swept away in the euphoria of educating children to be part of a faith-based effort to save her from straying from the black hole of cultural globalization. Integrated Islamic School became one of the institutions that were believed by the public to educate children in accordance with his religious beliefs, which was based on the power of the discourse of the Quran text. Cause public euphoria pragmatism hegemony in the religious life and discourse interpret the Qurâan text that should not only be part of the formal idol without the full meaning and understanding simple. Integrated Islamic School that raised public hegemony became part of religious education that had doctrinal side of the positive values that emphasize ethical moral teachings for the sake of public order and peace, but it could be different from that created by religious hegemony with power and dominance over his people. Religiosity practice known in the west as a new era of spirituality or postmodern spirituality. Dream institute which was expected to educate children to be part of the human being started based on religious values but becomes oppression and imprisonment for children. Determination of the values of the Qurâan made school teaching hours increase, so that integrated Islamic Â Education refers to the concept of a full - day school. Religious hegemony in the educational area to be part of the euphoria that saved the way education was becoming increasingly oppressive and merely a formality in meaning in performing religious beliefs that were considered sacred.